2012
DOI: 10.3109/09286586.2012.657765
|View full text |Cite
|
Sign up to set email alerts
|

Trachoma Prevalence in Women Living in Rural Northern India: Rapid Assessment Findings

Abstract: The results of our rapid assessment suggest that the presence of cicatricial trachoma remains an important health issue in females over 15 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Around three-quarters of the studied group were females representing 77.2% while males 22.8%, this goes in harmony with Khanduja (2012)[9] as his sample included one thousand females in underdeveloped parts of an Indian villages. Both studies showed approximately a prevalence of trachoma of 31% (in this study 31.1% while in Khanduja was 31.8%).…”
Section: Discussionsupporting
confidence: 73%
“…Around three-quarters of the studied group were females representing 77.2% while males 22.8%, this goes in harmony with Khanduja (2012)[9] as his sample included one thousand females in underdeveloped parts of an Indian villages. Both studies showed approximately a prevalence of trachoma of 31% (in this study 31.1% while in Khanduja was 31.8%).…”
Section: Discussionsupporting
confidence: 73%
“…This is the case in many programs, but the gender gap remains a problem in Oman, which may not successfully eliminate trachoma until coverage is more equal between men and women [40]. In underdeveloped communities of India, as many as one-third of women had trachoma symptoms, but only 40% received any treatment [112]. …”
Section: The Overall Effectiveness Of Safementioning
confidence: 99%
“…The success of various health programmes cannot be denied, but the trachoma persisted and now has shown upsurge, due to lack of awareness and interest by government agencies. Trachoma prevalence in India has been reported to be varying between 0.5 to 80 per cent, according to studies conducted across various centers [6][7][8][9][10][11][12][13]. Community studies were conducted to find out the true prevalence of Chlamydia trachomatis infection using laboratory support in the known hyperendemic belt of northern India by the Trachoma Study Group in 1998 (Uttar Pradesh) and later in 2007-2008 (Haryana) [5,9].. Sharma et al from RP Center, AIIMS did a twelve year study (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) in rural northern India and has shown the prevalence of trachoma to be persisting in northern India, albeit at a lower level [14].…”
Section: Discussionmentioning
confidence: 99%